Factories And Machinery ACT 1967 (ACT 139), Regulations & Rules (AS AT 10TH FEBRUARY 2012) - International Law Books Services; Legal Research Board (Petaling Jaya, Selangor : International Law Books Services, 2012)
Johor Corporation (JCorp);